Hyperventilation and Hypoxia Hangover During Normobaric Hypoxia Training in Hawk Simulator - Varis, Nikke; Leinonen, Antti; Parkkola, Kai; Leino, Tuomo K. (Frontiers in Physiology, 2022)
INTRODUCTION: In military aviation during high-altitude operations, an oxygen or cabin pressure emergency can impair brain function and performance. There are variations in individuals’ physiological responses to low partial pressure of oxygen and hypoxia symptoms can vary from one exposure to another. The aim of this study was to evaluate how normobaric hypoxia (NH) affects pilots’ ventilation rate and 10 minutes afterwards on Instrument Landing System (ILS) flight performance in Hawk simulator during a tactical flight sortie. METHODS: Fifteen volunteer fighter pilots from the Finnish Air Force participated in this double blinded, placebo controlled and randomized study. The subjects performed three flights in a tactical Hawk simulator in a randomized order with full flight gear, regulators and masks on. In the middle of the flight without the subjects’ knowledge, 21% (control), 8% or 6% oxygen in nitrogen was turned on. Minute ventilation (VE) was measured before, during NH and after NH. Forehead peripheral oxygen saturation (SpO2), wireless ECG and subjective symptoms were documented. The flights were conducted so that both subjects and flight instructors were blinded to the gas mixture. The pilots performed tactical maneuvers at simulated altitude of 20 000 ft or 26 000 ft until they recognized the symptoms of hypoxia. Thereafter they performed hypoxia emergency procedures with 100% oxygen and returned to base (RTB). During the ILS approach, flight performance was evaluated. RESULTS: The mean VE increased during NH from 12.9 L/min (21% O2 on the control flight) to 17.8 L/min with 8% oxygen (p<0.01), and to 21.0 L/min with 6% oxygen (p<0.01). Ten minutes after combined hyperventilation and hypoxia, the ILS flight performance decreased from 4.4 (control flight) to 4.0 with 8% oxygen (p=0.16) and to 3.2 with 6% oxygen (p<0.01). A significant correlation (r = -0.472) was found between the subjects’ VE during 6% oxygen exposure and the ILS flight performance. DISCUSSION: Hyperventilation during NH has a long-lasting and dose-dependent effect on the pilot’s ILS flight performance, even though the hypoxia emergency procedures are executed 10 minutes earlier. Hyperventilation leads to body loss of carbon dioxide and hypocapnia which may even worsen the hypoxia hangover.